2016
DOI: 10.1016/j.aquaculture.2015.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Early development of the blue mussel Mytilus edulis (Linnaeus, 1758) cultured in potassium-fortified inland saline water

Abstract: The low potassium concentration in inland saline water (ISW) restrains the normal development of cultured marine organisms, and thus, possesses challenges for the development of ISW aquaculture. Therefore, assessing the effects of potassium fortification in ISW on the performance of cultured marine species is an important step to determine the feasibility of their culture in ISW. The aim of this research was to investigate the effects of potassium fortification in ISW on the performance of early life stages of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
(72 reference statements)
0
8
0
Order By: Relevance
“…Therefore, a comparative study on the metabolic response to pH stress is necessary to develop a strategy to prevent crab mortality and subsequent economic loss under a chronic low or high pH stress. Our motivation to investigate the response of crab to pH stress was due to the development of saline-alkali water aquaculture in island saline water, which has been practiced worldwide, including in Thailand, Brazil, China, Mexico, Ecuador, the United States, and Vietnam ( Dinh, 2015 ). However, most studies on crustacean aquaculture at low salinity are mainly focusing on shrimp Litopenaeus vannamei ( Wang et al, 2015 , 2017 ; Chen et al, 2019 ) and the cultivation of crabs has not been reported ( Roy et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a comparative study on the metabolic response to pH stress is necessary to develop a strategy to prevent crab mortality and subsequent economic loss under a chronic low or high pH stress. Our motivation to investigate the response of crab to pH stress was due to the development of saline-alkali water aquaculture in island saline water, which has been practiced worldwide, including in Thailand, Brazil, China, Mexico, Ecuador, the United States, and Vietnam ( Dinh, 2015 ). However, most studies on crustacean aquaculture at low salinity are mainly focusing on shrimp Litopenaeus vannamei ( Wang et al, 2015 , 2017 ; Chen et al, 2019 ) and the cultivation of crabs has not been reported ( Roy et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because soil salinization represents a severe threat to human survival and development, it has attracted worldwide attention. Several statistical investigations have shown that 9.55 × 10 8 hm 2 of soil is under threat of salinization across the globe [10,11]. This amounts to approximately 20% of the global total of arable land spread over more than 100 different countries.…”
Section: Introductionmentioning
confidence: 99%
“…This amounts to approximately 20% of the global total of arable land spread over more than 100 different countries. The area affected by secondary salinization is about 0.77 × 10 8 hm 2 and is growing at a rapid rate [10,11]. Traditional laboratory chemical analysis requires the excavation and collection of soil samples as well as transportation to a laboratory for analysis, which damages the soil, Moreover, this method is time consuming, labor intensive, and has a high testing cost [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…ISW aquaculture is now practiced worldwide, where it was inspired by the success of Litopenaeus vannamei aquaculture in Thailand using a brine solution ( Roy et al, 2010 ), which expanded worldwide subsequently, including in Brazil, China, Ecuador, Mexico, Thailand, the United States, and Vietnam ( Dinh, 2015 ). However, the cultivation of shellfish in ISW has been only reported sporadically, such as with Mytilus edulis ( Dinh and Fotedar, 2016 ), Haliotis laevigata ( Doupé et al, 2003 ), Trochus niloticus ( Lee, 1997 ), Crassostrea gigas , and Saccostrea glomerata ( Ingram et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%